Increased tolerance of economic-based societies - Mujahidin, Endin; Shinta Aminda, Renea; br Ginting, Novita (Technium Social Sciences Journal, 2022)
The purpose of this study is to increase the tolerance of economic-based societies by using this type of experimental learning research, which is a study by explaining the needs by describing past, present and future variables. The subjects in this study were students of Al-Ittihadiyah Junior High School and santri Pondok Pesantren As Salaam Data collection technique is the most important step in the research, because the main purpose of the research is to obtain data. So the techniques or methods used include observation, interviews, and documentation, the result of this study is the need to do assistance and increase economic-based tolerance in Al-itihadiyah Junior High School and santri pondok pesantren As salam.